Implementation of Roll Control on Mini Remotely Operated Vehicle - Andi Sugandi; Simon Siregar; Lisda Meisaroh (IJAIT (International Journal of Applied Information Technology), 2021)
This paper describes the design and manufacture of an underwater explorer robot. The proposed Mini Remotely Operated Vehicle (ROV) is designed to be controlled remotely using a wireless communication module outside the water. ROV stability is needed to support the operation of ROV when do maneuvering in the water. The design of the ROV is aimed to maintain stability using a PID control system. Moreover, the gain PID values, kP gain, kI gain, and kD gain, must be set to perform roll stability. After performing a fine-tuning of the PID gain values, the experiment result shows that the system can maintain an average error of -1.70 degrees.